Barriers to the Implementation of Food Safety and Hygiene Principles (HACCP) in TVET and University Hospitality Schools in Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the barriers to food safety and hygiene principles (HACCP) in TIVET and University hospital schools in Kenya. A total of 671 respondents participated in the study (Comprising 249 from universities, 250 from Institutes of Technology, 64 from Polytechnics and 128 from Technical Institutions). Primary data sources included using structured questionnaires, taking photographs, oral interviews, observation check list and focus group discussions. Secondary sources, on the other hand, involved retrieving information from desk research where journals, books and other relevant literature were obtained. Both descriptive and inferential statistics were used to analyze the quantitative data while content analysis was used to analyze the qualitative data. The analyzed data were presented in terms of graphs and tables. The findings revealed that 31% of the respondents admitted that there were barriers. Among the barriers were: lack of knowledge (32%), lack of set standards (31%), attitude (31%), lack of time (28%), lack of motivation (27%) lack of experience (26%), lack of facilities (23%) and inadequate equipment (23%). The study concluded that various factors such as lack of knowledge, attitude, lack of motivation and inadequate facilities and equipment posed serious threats to effective implementation of proper food safety system (HACCP). It was recommended that HACCP prerequisites related to institutional facilities are put in place and stakeholders trained on adherence to the principles.